Smart Jacket Sebagai Penerapan Physical Distancing - Robby Darwis; Sayuti Rahman; Arnes Sembiring (Universitas Harapan Medan, 2021)
Covid-19 entered Indonesia on Monday, March 2, 2020, to be precise in the city of Depok, West Java. The worsening of the Covid-19 outbreak in Indonesia has made the government give an appeal to the public to implement 3M as a prevention of Covid-19 in Indonesia. Distance or physical distancing is an advice from the government. In its application, one must wear a mask, wash hands and maintain a distance of at least 1 meter. The impact of the Covid-19 outbreak, activities in Indonesia have become completely paralyzed starting from March 2020. One of them is in education. During the pandemic, the Indonesian government through the Ministry of Education and Culture made a policy for schools and universities to carry out teaching activities boldly, because many parents/guardians felt these activities were very irrelevant. The closure of schools and universities has a clear negative impact on health, education and development. To overcome this, a warning tool is needed to implement physical distancing in face-to-face learning with a smart jacket using an Arduino Uno microcontroller, ultrasonic sensor, PIR sensor, buzzer and LCD i2c. The results of the test and implementation of this system are when an object approaches less than 100 cm. it will activate the buzzer as a warning to users and objects to apply physical distancing and the i2c LCD as distance information and warnings in the form of objects. From the results of testing this tool works well and is able to overcome the problems experienced by the community